Systematic Literature Review Penelitian Hydrothermal Cangkang Telur Ayam dengan Analisis Bibliometrik Menggunakan Software VOSviewer - Agusty, Muhammad Naufal; Etih Hartati; Djaenudin; Herlian Eriska Putra (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Food waste management is a global challenge that encourages the application of the circular economy concept through resource reuse. Chicken eggshell waste has the potential to be used as a renewable source of calcium, while hydrothermal processing is a promising method for converting it into value-added products. This study aims to map the development of hydrothermal processing research on chicken eggshell waste through a bibliometric analysis of 75 Scopus-indexed publications from 2019 to 2024. The results of the analysis show that China is the country with the highest number of publications. Co-authorship analysis identified 27 collaborating authors, with Zhang, X., Yin, J., and Wang, I. as the main authors. The most dominant keywords were “hydroxyapatite,” “hydrothermal method,” and “calcium.” This study shows that hydrothermal research focuses on the development of calcium-based biomaterials and nanomaterials and opens up opportunities for further research on the sustainable use of chicken eggshell waste.